Restraint of Starch-hydrolyzing Enzyme in the Management of Postprandial Blood Glucose Level: An Alternative Approach - Sani, Deedarul H.; Sarker, Parth; Alam, Md. Jahangir (Letters in Drug Design & Discovery, 2024)
Background: Diabetes is a multifaceted metabolic condition defined by postprandial hyperglycemia with perturbances in the majority of the metabolic systems in the human body. α-amylase is a key enzyme present in pancreatic juice and saliva that converts one of the common food sources i.e., starch molecules into absorbable molecules and raises plasma glucose levels. Reducing starch digestion by the inhibitors of starch hydrolyzing enzymes could be an intriguing strategy for improved postprandial hyperglycemia management. Objective: The present research work was undertaken to evaluate the inhibition potential of natural inhibitors of α-amylase from Trichosanthes dioica (pointed gourd) and Moringa oleifera (moringa leaves) extracts in vitro. Furthermore, in vivo cytotoxicity assessment was also conducted through brine shrimp lethality bioassay. Methods: Different organic solvents (namely acetone, ethanol, and methanol) were used to isolate plant extracts. DNS (3,5-dinitrosalicylic acid) was used to conduct the α-amylase inhibition assay. The safety of the natural inhibitors was determined by the most common technique i.e, brine shrimp lethality bioassay. Results: Among all the different organic solvent extracts, pointed gourd and its peel exhibited the highest α-amylase inhibition activity (64.03 ± 7.33–69.40 ± 9.38%) which is very close to standard α-amylase inhibitor acarbose (72.34 ± 4.23%) whereas moringa leaves showed moderate inhibition activities (59.10 ± 5.25–62.03 ± 1.77%). The cytotoxicity of pointed gourd and its peel was higher while moringa leaves demonstrated lower toxicity. Conclusion: Considering the inhibition rate and cytotoxicity, pointed gourd ethanol extract (Inhibition: 67.43 ± 11.80%; Cytotoxicity: 209.98 μg/mL) would be the best candidate for managing postprandial hyperglycemia.
Keywords: α-amylase